Forging Forms of Authority through the Sociomateriality of Food in Partial Organizations. Issue 2 (February 2021) - Pascucci, Stefano; Dentoni, Domenico; Clements, Jen; Poldner, Kim; Gartner, William B.
This study theorizes on the sociomateriality of food in authority-building processes of partial organizations by exploring alternative food networks (AFNs). Through the construction of arenas for food provisioning, AFNs represent grassroots collectives that deliberately differentiate their practices from mainstream forms of food provisioning. Based on a sequential mixed-methods analysis of 24 AFNs, where an inductive chronological analysis is followed by a qualitative comparative analysis (QCA), we found that the entanglements between participants' food provisioning practices and food itself shape how authority emerges in AFNs. Food generates biological, physiological and social struggles for AFN participants who, in turn, respond by embracing or avoiding them. As an outcome, most AFNs tend to bureaucratize over time according to four identified patterns while a few idiosyncratically build a more shared basis of authority. We conclude that the sociomateriality of food plays an important yet indirect role in understanding why and how food provisioning arenas re-organize and forge their forms of authority over time.